2016
DOI: 10.1016/j.jss.2016.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Severe burn increased skeletal muscle loss in mdx mutant mice

Abstract: Background-Severe burn causes muscle mass loss and atrophy. The balance between muscle cell death and growth maintains tissue homeostasis. We hypothesize that pre-existing cellular structural defects will exacerbate skeletal muscle mass loss after burn. Using a Duchenne muscular dystrophy (mdx) mutant mouse, we investigated whether severe burn caused more damage in skeletal muscle with pre-existing muscle disease.Methods-The mdx mice and wild type mice received 25% total body surface area (TBSA) scald burn. Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Plasma HMGB1 levels were increased in patients with burn on > 10% TBSA at the time of hospitalization, and the secreted HMGB1 levels correlated with burn size and poor survival outcomes in burn patients 18 . HMGB1 level in gastrocnemius lateral muscle of rats exposed to burn on 30% TBSA (vs. sham burn) was increased by 164.80%, similar to what was observed in our previous study of burn mouse model 37 and treatment with HMGB1 Ab improved the muscle mass in burn rats. These findings provide evidence for the pathological role of burn induced systemic increase in HMGB1 in muscle loss and imply that HMGB1 neutralization will prevent the muscle mass loss and muscle wasting after burn.…”
Section: Discussionsupporting
confidence: 88%
“…Plasma HMGB1 levels were increased in patients with burn on > 10% TBSA at the time of hospitalization, and the secreted HMGB1 levels correlated with burn size and poor survival outcomes in burn patients 18 . HMGB1 level in gastrocnemius lateral muscle of rats exposed to burn on 30% TBSA (vs. sham burn) was increased by 164.80%, similar to what was observed in our previous study of burn mouse model 37 and treatment with HMGB1 Ab improved the muscle mass in burn rats. These findings provide evidence for the pathological role of burn induced systemic increase in HMGB1 in muscle loss and imply that HMGB1 neutralization will prevent the muscle mass loss and muscle wasting after burn.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies demonstrated that the pathophysiological response to burn injury alters the balance between skeletal muscle protein anabolism and catabolism [ 10 ]. This results in immediate loss of skeletal muscle mass [ 11 13 ]. Interestingly, it was shown that burn injury results in atrophy and myogenesis stimulation in muscle due to a host systemic response, although myogenesis does not compensate for burn-induced cell death [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrocnemius tissue contains mixed slow-and fast- myofiber types, and its anatomic location is far away from burn wound site in mouse trunk. We and others analyzed the gastrocnemius tissue to represent the muscle response to systemic influence in mouse and rat models 38 , 39 . Gastrocnemius tissues (~ 25 mg) were processed for total RNA extraction using Qiagen RNeasy Mini Kit (Germantown, MD).…”
Section: Methodsmentioning
confidence: 99%